Spiritual leadership and teacher well-being in primary and secondary schools: the mediating role of teachers’ trust in leaders and organizational justice - Jing Li; Nana Jiang; Shuang Li; Xiaodong Peng; Man Li; Wei Zhang; Lai-Kuan Kong; Soon-Yew Ju (BMC Psychology)
Abstract Background Teacher well-being in primary and secondary schools is crucial to ensuring sustainable development in the field of education, and it is an important topic that needs attention in the management of primary and secondary schools in China. The leadership style of school administrators plays a key role in enhancing teacher well-being. This study aimed to explore the mechanism of spiritual leadership on teacher well-being and to test the mediating effects of teachers’ trust in leaders as well as organizational justice in this relationship. Methods This study utilized a non-probability purposive sampling method and a web-based questionnaire to survey 311 primary and secondary school teachers in China. In order to validate the research model, this study used Partial Least Squares Structural Equation Modeling (PLS-SEM) and analyzed the collected data using SmartPLS 4.0 software. Results It was found that spiritual leadership positively and significantly affected teacher well-being. Teachers’ trust in leaders played a positive mediating role between spiritual leadership and teacher well-being. Although spiritual leadership positively and significantly affected organizational justice, organizational justice did not have a significant effect on teacher well-being, and lastly, the mediating effect of organizational justice between spiritual leadership and teacher well-being was not supported. Additionally, the variables of spiritual leadership, teachers’ trust in leaders, and organizational justice collectively explained 47.9% of the variance in teacher well-being. Conclusions The findings enriched the research on spiritual leadership and teacher well-being and deepened the understanding of the relationship between them. Spiritual leadership should be actively cultivated and promoted in primary and secondary school management practices to enhance teachers’ trust in leaders, thereby effectively enhancing teacher well-being in primary and secondary schools.